Asthma control in children: Is it important and can we measure it?. (January 2016) - Pedersen, Søren
Summary: The goal of asthma management is to achieve disease control. Poorly controlled asthma is associated with an increased number of days lost from school, exacerbations and days in hospital. Furthermore, children with uncontrolled asthma have more frequent contacts with the health-care system. Recent studies have added new information about the effects of poorly controlled asthma on a range of important, but less studied outcomes, including risk of obesity, daily physical activity, cardiovascular fitness, stress, concentration and focused attention, learning disabilities and risk of depression. From these studies it seems that poor asthma control may have a greater impact on the child than previously thought. This may have important long-term consequences for the child such as an increased risk of life-style associated diseases and poorer school performance. The level of control seems to be the most important determinant of these adverse effects and improvement in asthma control is associated with improvements in many of the outcomes. However, the improvement has to be maintained for a very long time (> 1 year). Accurate assessment of the level of asthma control is difficult. Various tools and scores have been developed. They are all based on various questionnaires, but their validation has been difficult because we have no golden standard to compare with. It seems as if the tests are most valuable when they suggest that the disease is poorly controlled because a large proportion of children in whom the tests suggest good asthma control may still have poorly controlled asthma when various objective outcomes are included in the assessment. A main reason for that seems to be that none of the tests accurately detects the child's adaptation in lifestyle. If you do not exercise you have fewer symptoms.